If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x = 40 + 10x Solving 20x = 40 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 20x + -10x = 40 + 10x + -10x Combine like terms: 20x + -10x = 10x 10x = 40 + 10x + -10x Combine like terms: 10x + -10x = 0 10x = 40 + 0 10x = 40 Divide each side by '10'. x = 4 Simplifying x = 4
| 17j-6j+2j-5j-j=7 | | 0=-12x^2-1560x-48000 | | x/x-8=24-2x/x-8 | | -27=-5x-2(-3+18) | | 0.083x-0.083=0.125+0.16-0.16x | | -3x+2y=-14 | | 12p^2-45p-9=3 | | 3q-3q+4q=20 | | 2x+41= | | 2(2x-3)=34 | | w+5w+w-6w=18 | | 1.2=(1+k)6 | | 9.7=-0.01x^2+0.26x+8.65 | | 10r=gr+38 | | 16k-14k=14 | | 2x+10y+5z=30 | | 300-7[4(3+5)]+9= | | 3x+4.5=4.5-18 | | 250+410=0.08 | | x^2+6y=-1 | | 101=2x+3x | | x+(x+1)+(x+2)+(x+3)+(x+4)= | | 6r-5r=14 | | 10x/x | | x(3x-4)-7=0 | | 8(x-1)(3x-1)=0 | | 250+0.08=410 | | 2(2x+3)-7x=-5(x+3x) | | (x+4)(x-12)-5x=0 | | 9*2x=10(x+8) | | 112=4+96x-16x^2 | | 4x-4=-46-3x |